Factors affecting the safety performance in portuguese construction: summary analysis focused on rehabilitation works - Couto, J. Pedro (2013)
The accidents in the construction are one of the main indicators of the claims recorded at work in Portugal. The identification of the factors and causes related with accidents at work is essential for a correct analysis of the risks and a consequent adoption of procedures and measures to achieve a more effective prevention. The focus on rehabilitation has increased in Portugal and it is in this kind of construction that accidents are more frequent, mainly motivated by the lack of local knowledge to work and skilled manpower. Thus, on the basis of an inquiry implemented to several categories of interveners, this work puts forward the main reasons for noncompliance in safety regarding this type of activity.